High Prevalence of Spinal Magnetic Resonance Imaging Findings in Asymptomatic Young Adults (18–22 Yrs) Candidate to Air Force Flight. Issue 12 (15th June 2019) - Romeo, Valeria; Covello, Mario; Salvatore, Elena; Parente, Chiara Anna; Abbenante, Domenico; Biselli, Roberto; Ciriello, Mattia; Musolino, Pasquale; Salvatore, Marco; Cangiano, Alessandro
Abstract : Study Design: Cross-sectional, retrospective, magnetic resonance (MR) imaging study, performed during cadets' selection procedures of the Italian Air Force Academy. Objective: To assess the prevalence of spinal MR imaging findings in asymptomatic young adults (18–22 yrs) candidate to Air Force Flight. Summary of Background Data: Spinal MR imaging findings are frequently detected in asymptomatic subjects. Literature prevalence data come from studies that analyze different patient populations, in a wide age range and in different spinal tracts. Chronic degenerative disease of the vertebral column often occurs in pilots exposed to high flight acceleration forces, thus resulting crucial for Air Force Academy to exclude vertebral disease in cadets. Methods: Three hundred fifty asymptomatic young adults underwent a 3T MR examination of the entire spine. A structured radiological report was set up to classify and calculate the prevalence of spinal MR imaging findings. Results: Two hundred seventy of 350 subjects (77%) presented spinal MR findings, while 80 of 350 candidates (23%) had no detectable MR imaging findings. One hundred six of 350 (30%) candidates had at least one disc desiccation and 47 of 350 (13%) presented at least one disc narrowing. Disc bulging was found in 176 of 350 (49%) cadets. Sixty-two of 350 (18%) subjects showed disc protrusion while 28 of 350 (8%) had disc extrusion. Forty-five of 350 (13%) candidates presented low grade intervertebral spondylosis and of these 12 had also facet joints spondylosis. Asymptomatic vertebral fractures were observed in 2 of 350 (<1%) cadets. Conclusion: A high rate of MR spinal imaging findings, similar to that of the adult population, was detected in our population of young asymptomatic subjects. Our results suggest that the process of aging spine, which is supposed to begin in the second decade of life, is morphologically appreciable in the immediate postadolescent period and this issue is of crucial importance when selecting military pilots. Level of Evidence: 4 Abstract : A high prevalence of spinal MR imaging findings was found in asymptomatic young adults (18–22 yrs) candidate to Air Force Flight. These findings suggest that the process of aging spine is morphologically appreciable in the immediate postadolescent period and this issue is of crucial importance when selecting military pilots.